2021
DOI: 10.1684/epd.2021.1307
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lacosamide in neonatal‐onset super‐refractory status epilepticus: a case report

Abstract: We report the case of a previously healthy newborn who developed super‐refractory status epilepticus after Group B streptococcal meningoencephalitis. After administration of first‐, second‐ and third‐line anticonvulsants without resolution of status epilepticus, we started intravenous lacosamide as adjunctive therapy to phenobarbital, phenytoin and continuous infusion of ketamine and midazolam. After administration of lacosamide, we observed a clear‐cut improvement in the neurological clinical condition couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16] To date, the largest study on pediatric use of IV LCM included 47 children, 9,12 and two case reports described the efficacy of IV LCM in nonneonatal infants with refractory status epilepticus. 10,16 One case report described efficacy of oral LCM in a 3-week-old infant, but did not specifically report AEs. 17 Although a recent case series reported the absence of teratogenic findings in neonates born to mothers with epilepsy who were taking LCM during pregnancy, 18 no studies have evaluated the safety of IV LCM in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] To date, the largest study on pediatric use of IV LCM included 47 children, 9,12 and two case reports described the efficacy of IV LCM in nonneonatal infants with refractory status epilepticus. 10,16 One case report described efficacy of oral LCM in a 3-week-old infant, but did not specifically report AEs. 17 Although a recent case series reported the absence of teratogenic findings in neonates born to mothers with epilepsy who were taking LCM during pregnancy, 18 no studies have evaluated the safety of IV LCM in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Although oral LCM has been shown to be generally effective and well tolerated by children with epilepsy, 5 few studies describe the effects of IV LCM in children. [9][10][11][12][13][14][15][16] To date, the largest study on pediatric use of IV LCM included 47 children, 9,12 and two case reports described the efficacy of IV LCM in nonneonatal infants with refractory status epilepticus. 10,16 One case report described efficacy of oral LCM in a 3-week-old infant, but did not specifically report AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were anesthetized with isoflurane and decapitated per approved protocol. The brain was placed in icecold artificial cerebrospinal fluid (aCSF) containing (in mmol•L −1 ) NaCl (120), KCl (3.3), CaCl 2 (1.3), MgCl 2 (2), NaH 2 PO 4 (1.25), NaHCO 3 (25), and D-glucose (10) with a pH of 7.3-7.4 when bubbled with 95% O 2 and 5% CO 2 . Coronal brain slices, 450 μm (pups) and 350 μm (adults) thick, were cut using a vibratome (Leica VT1000S) while submerged in aCSF containing 2 mmol•L −1 kynurenic acid to block glutamatergic receptors.…”
Section: Acute Brain Slice Preparationmentioning
confidence: 99%
“…It works by enhancing the slow inactivation of voltage‐gated sodium channels 23,24 . Although lacosamide is not commonly used to treat neonatal seizures, some neurologists use it to treat refractory neonatal seizures only as a fourth or fifth choice 25,26 . However, no studies have evaluated lacosamide's effectiveness in treating neonatal seizures in humans or mice, and it is unclear whether lacosamide alters the incidence of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 It has been shown to successfully terminate seizures in adults and children, with recent case studies demonstrating efficacy in neonates. 5,6 Its efficacy mixed with tolerable common side effects (occasional dizziness, somnolence, nausea and vomiting, headaches, diplopia, and dyskinesias) 3,7 has made it more popular in recent years. 8 Although many studies have found lacosamide to be a safe medication with mild side effects, 3,[8][9][10][11][12] there are also a handful of case studies that note significant cardiac events, most related to prolongation of the PR interval.…”
mentioning
confidence: 99%